PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI SDN 012 SILIKUAN HULU - Ngantiyem ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This study was based behind the poor performance of students learning IPS. This is evidencedby the percentage of students learning completeness of 29.42%. This study aims to improvescience learning outcomes of students through direct learning model application. Thisresearch is a class act, to which the data focuses on learning outcomes for science students.Based on the results of the study, stated that science learning outcomes of students hasincreased in the first cycle improving student learning outcomes reached 70%. After thesecond cycle increased with the achievement of 85%.